Teacher Professional Development in the 21st Century - AbdulRab, Hanan (African Journal of Education and Practice, 2023)
Purpose: Professional development of teachers is a lifelong process which begins with the initial preparation that teachers receive and continues until retirement. The importance of teacher professional development stems from the fact that teachers are the most important change agents in the educational system. This paper investigates teacher professional development in the 21st Century in terms of the three theories: constructivism theory, adult learning theory and transformational leadership theory. Methodology: This theoretical paper draws from the three theories: constructivism theory, adult learning theory and transformational leadership theory to outline approaches for teacher professional growth in the 21st century. Based on a review of literature, there are new models and chances to develop teacher professional development for 21st Century education. Findings: Continuing professional development of teachers helps them to become better teachers by acquiring new skills and improving their competencies. Unique Contribution to Theory, Practice and Policy: This study highlighted effective methods of teacher professional development for 21st century education and emphasized the positive impact of such methods and approaches on the growth and development of teachers in an era characterized by rapid technological advancements and changing educational paradigms. All these approaches and methods are supported by the three theories: constructivism theory, adult learning theory and transformational leadership theory.